Maternal risk factors for stunting in children aged 24-59 months - Dayani, Tiara Rica; Widyantari, Kadek Yuke (Intelektual Pustaka Media Utama, 2024)
Stunting is a problem of growth and development disorders in children which is related to nutritional problems in the world. In 2022, 21.6% of children aged under five years in Indonesia were stunted. Several factors influence stunting, including environmental (social), household factors, maternal and child factors. The aim of this study was to determine maternal risk factors for stunting in children aged 24 to 59 months. This research, with a case control study design, involved 191 participants (91 stunted children and 100 non-stunting children). The results found that maternal factors associated with stunting in children aged 24-59 months included maternal height (P<0.005, OR 2.025), birth spacing (P<0.005, OR 1.912), gestational age (P<0.005, OR 2.622), history of illness during pregnancy (P<0.005, OR 2.453), and consumption of iron tablets during pregnancy (P<0.001, OR 7.600). In the multivariate analysis, consumption of iron tablets and maternal height were the factors identified as being most related to the incidence of stunting in children aged 24-59 months.